The role of the multidisciplinary tumor board (MDTB) in the assessment of pancreatic cancer diagnosis and resectability: A tertiary referral center experience - Quero, Giuseppe; De Sio, Davide; Fiorillo, Claudio; Menghi, Roberta; Rosa, Fausto; Massimiani, Giuseppe; Laterza, Vito; Lucinato, Chiara; Galiandro, Federica; Papa, Valerio; Salvatore, Lisa; Bensi, Maria; et al. (Frontiers in Surgery, 2023)
Background The introduction of multidisciplinary tumor boards (MDTBs) for the diagnostic and therapeutic pathway of several oncological disease significantly ameliorated patients' outcomes. However, only few evidences are currently present on the potential impact of the MDTB on pancreatic cancer (PC) management. Aim of this study is to report how MDTB may influence PC diagnosis and treatment, with particular focus on PC resectability assessment and the correspondence between MDTB definition of resectability and intraoperative findings. Methods All patients with a proven or suspected diagnosis of PC discussed at the MDTB between 2018 and 2020 were included in the study. An evaluation of diagnosis, tumor response to oncological/radiation therapy and resectability before and after the MDTB was conducted. Moreover, a comparison between the MDTB resectability assessment and the intraoperative findings was performed. Results A total of 487 cases were included in the analysis: 228 (46.8%) for diagnosis evaluation, 75 (15.4%) for tumor response assessment after/during medical treatment, 184 (37.8%) for PC resectability assessment. As a whole, MDTB led to a change in treatment management in 89 cases (18.3%): 31/228 (13.6%) in the diagnosis group, 13/75 (17.3%) in the assessment of treatment response cohort and 45/184 (24.4%) in the PC resectability evaluation group. As a whole, 129 patients were given indication to surgery. Surgical resection was accomplished in 121 patients (93.7%), with a concordance rate of resectability between MDTB discussion and intraoperative findings of 91.5%. Concordance rate was 99% for resectable lesions and 64.3% for borderline PCs. Conclusions MDTB discussion consistently influences PC management, with significant variations in terms of diagnosis, tumor response assessment and resectability. In this last regard, MDTB discussion plays a key role, as demonstrated by the high concordance rate between MDTB resectability definition and intraoperative findings.